Cytogenetic alterations in human lymphocyte culture following exposure to radiofrequency field of mobile phone - Sabah F. El-Abd, Marwa Y. Eltoweissy (Journal of Applied Pharmaceutical Science)
The present study aims to address the possible cytogenetic effect of mobile phone on human lymphocyte culture. Human peripheral blood cultured from healthy, non-smoking donors exposed to 1950 MHz and safety limit (2w/kg) of absorption rate (SAR) mobile radiofrequency radiation for 5, 10, 15, 20, 25 and 30 min, then harvested after 24 hr after subjection. The alkaline comet assay, chromosomal aberrations and the micronucleus test were used, to check for changes, stress response and alterations in lymphocytes. The result indicated the presence of timedependant cellular response to RF exposure of mobile phone kept in the standby position, through comet tail factor, DNA fragmentation, chromosomal aberrations and centromeric negative nuclei (MN) in human lymphocyte culture. This effect may be attributed to oxidative stress induced by mobile phone radiation.
Keywords: Mobile phone, Genetic alteration, Comet Assay, Chromosomal aberrations, Micronucleus.